Analisis Gap Penerapan Sistem Manajemen Mutu 9001:2015 PT. Gaya Teknik Logam - Tofik Hidayat; Zulfah; Dwi Nurhidayani (Journal of Research and Technology, 2022)
Gaya Teknik Utama (GTU) is SMEs supplier AHM, which produces sparepart. SMEs must follow very strict standards in quality, both product quality and quality management system. The quality of Tegal SME products has been proven, however, QMS still needs to be improved and monitored. PT. GTU has implemented QMS ISO 9001:2015 to guarantee its products. The implementation of the ISO 9001 QMS is not easy because it requires the thoroughness and commitment of all parties, from the leadership to the cleaning staff. This study intends to look at the gaps in the implementation of QMS mainly in clauses 6, 8, 9 and 10. The research used descriptive qualitative methods, observations and interviews. The results of the research and analysis of clauses 6, 8, 9 and 10 show that the implementation of the ISO 9001:2015 QMS is still not good. The research recommendation is in the form of a proposed improvement in clause 6, namely considering the application of Specific, Measurable, Agreed, Reasonable, Time-Bound as a measuring tool. Clause 8 preparation of quality documents for planning and control procedures for raw materials, reports on production and defective products, procedures related to handling output control. Clause 9 improvements by making a questionnaire form to customers to measure customer satisfaction, planning training schedules and conducting internal quality audits and periodic management reviews. Clause 10 proposed quality document improvement.